New records of Dacrymyces ovisporus and Tremella diaporthicola from the Ukraine - Malysheva, V.; Akulov, A. (My University, 2011)
The present paper deals with new records of the heterobasidioid fungi Dacrymyces ovisporus Bref. and Tremella diaporthicola Ginns et M.N.L. Lefebvre in Europe. The taxonomical status of these species is considered and detailed descriptions and illustrations of specimens are given.
Keywords: heterobasidiomycetes; new records; Dacrymyces ovisporus; Tremella diaporthicola; Ukraine